Sketching from the imagination : creatures and monsters - Lewis, Marisa; Williams, L. A. (Lawrence Allen), 1965- (Worcester, United Kingdom : 3dtotal Publishing, 2019)
"In this inspiring addition to the popular Sketching from the Imagination series, we invite readers to explore the works of fifty artists from across the field of creature design. From magical and mythical beasts to aliens and mutant monsters, each page comes alive with wild and wonderful creations in a range of styles and mediums. Each artist offers their personal commentary, advice, and tips on drawing techniques and concept design processes, making Sketching from the Imagination: Monsters & Creatures a rich and exciting volume for any reader, whether they're looking for an intriguing menagerie of artwork to browse, or for artistic and professional insights by a wide range of talented and imaginative creators."--Amazon.com
Table Of Contents: Foreword Antoniou, Antonios (Noxis) Bakhareva, Ksenia Bang, William Bertet, Janine Bialek, Stella Bruderer, Alice Camehl, Tony Chen, Longque Coviello, Vincent Durmisevic, Edin Faure, Stephane (Beesub) Fernandez, Julia Fortt, Anthony (Moa) Frankova, Petra Fratean, Raluca (Ralukko) Frontoni, Giulia Gheneli, Vlad Gish, Daniel Ha, Seungeun (Hawdy) Hamel, Charles Henriksen, Maria Hristova, Polina Inkognit Jako, Mate Juteau, Virginie Kim, Jaemin Kim, Sorie Kotaki, Kekai Kuo, Jonathan Lexova, Kristina Lovejoy, Evan Menendez, Oriana Ostrowski, Alexander Park, JiHoon Pauselli, Laura (Fulemy) Plutowska, Karolina (Isvoc) Powell, Carissa Kaye Prime, April Rebholz, Bobby Rodriguez, Arthur Schutte, Audre (Charamath) Solomon, April Spala, Hubert Tew, Jin Yee Tiefer, Josh Trevino, Robbie Ulksy Vassie, Dominique Walker, Jordan K Yastrubetskaya, Ekaterina Contributors
Keywords: Monsters in art; Animals, Mythical, in art; Drawing -- Technique